The Antioxidant Capacity of Rosemary and Green Tea Extracts to Replace the Carcinogenic Antioxidant (BHA) in Chicken Burgers - Manoela A. Pires; Paulo E. S. Munekata; Nilda D. M. Villanueva; Fernando G. Tonin; Juliana C. Baldin; Yana J. P. Rocha; Larissa T. Carvalho; Isabela Rodrigues; Marco A. Trindade (Journal of Food Quality)
The present study aimed to evaluate the effect of natural extracts (rosemary and green tea extracts) in frozen storage of chicken burgers. Chicken burger treatments were prepared as follows: control (CON), 20 mg BHA/kg (BHA20), 10 mg green tea extract/kg (GT10), 38 mg green tea extract/kg (GT38), 18.6 mg rosemary extract/kg (RO18), and 480 mg rosemary extract/kg (RO480). Analysis of physicochemical parameters, color, TBAR index, and sensory acceptance were performed at 0, 30, 60, and 120 days of storage at −18°C in burgers packaged in LDPE plastic bags. The addition of natural antioxidants did not affect (p>0.05) the color and physicochemical parameters of the chicken burgers. After 120 days at −18°C, the RO480 sample showed a TBAR index similar (p>0.05) to BHA20 (0.423 and 0.369 mg, resp.). Sensory acceptance did not differ (p>0.05) among the treatments throughout the storage period (p>0.05).